Outcomes after rotator cuff repair in the elderly as assessed by the American Shoulder and Elbow Surgeons shoulder score - Yushun Fang; Qingsong Zhang (Clinics)
Rotator cuff tears are common among the elderly, and studies on the outcomes after rotator cuff repair in the elderly are limited. We carried out this meta-analysis with systematic literature search, aiming to clarify the outcomes after rotator cuff repair in the elderly as assessed by the American Shoulder and Elbow Surgeons (ASES) shoulder score. We conducted a literature search through October 2019 in PubMed and EMBASE databases and performed meta-analysis to calculate the summary mean difference comparing the post- and pre-operation ASES scores under both fixed-effect and random-effect models. Among 4978 studies identified through literature search, four studies (two in the United States, one in France, and one in Republic of Korea) were eligible for the meta-analysis, including 282 patients who were aged over 70 years. These studies had low heterogeneity as measured by Cochran’s Q test (p=0.88) and I2 statistic (0%). The ASES scores on average increased by 39.7 (95% confidence interval 28.3-51.1, p<0.001) after rotator cuff repair, in both fixed-effect and random-effect models. No substantial publication bias was indicated. Our findings suggest improved outcomes after rotator cuff repair in the elderly population as measured by the ASES score, and such improvements have been consistent in previous studies.